2016
DOI: 10.4103/0972-5229.190369
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum interleukin-6, interleukin-8, and Acute Physiology and Chronic Health Evaluation II score with clinical outcome in patients with acute respiratory distress syndrome

Abstract: Background and Aim:Studies on potential biomarkers in experimental models of acute lung injury (ALI) and clinical samples from patients with ALI have provided evidence to the pathophysiology of the mechanisms of lung injury and predictor of clinical outcome. Because of the high mortality and substantial variability in outcomes in patients with acute respiratory distress syndrome (ARDS), identification of biomarkers such as cytokines is important to determine prognosis and guide clinical decision-making.Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…IL-6 is a potent pro-inflammatory cytokine that plays a key role in the pathogenesis of various inflammatory disorders, such as ARDS. Increased levels of both IL-8 and IL-6 have been shown to be highly correlated with the incidence of ARDS and overall mortality [ 72 74 ]. The concomitant increase in IFN-γ following IL-12 secretion by hMSCs under hypoxia was expected since IL-12 promotes the production of IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a potent pro-inflammatory cytokine that plays a key role in the pathogenesis of various inflammatory disorders, such as ARDS. Increased levels of both IL-8 and IL-6 have been shown to be highly correlated with the incidence of ARDS and overall mortality [ 72 74 ]. The concomitant increase in IFN-γ following IL-12 secretion by hMSCs under hypoxia was expected since IL-12 promotes the production of IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips et al [ 31 ] had shown that the lung injury score of non-survivors was significantly higher than that of survivors in patients with ARDS. Swaroopa et al [ 32 ] had shown that the APACHE II score was significantly higher in non-survivors as compared to survivors in patients with ARDS. In this study it was found that the APACHE II, ALIS, PaO 2 /FIO 2 and AaDO 2 were not significantly different between the survived and non-survived ARDS patients; instead, the HFP and TP were found to be the independent predictors of mortality in ARDS patients on admission to the SICU ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.1371/journal.pbio.3000970.g003 prognoses of acute respiratory distress syndrome and sepsis using IL-6 expression levels have also been established [55][56][57]. IL-6 also has a significantly increased expression level in the human bronchial epithelial cells infected with SARS-CoV-2 from the SARS2-DEG dataset [21].…”
Section: Network-based Measurement Of Covid-19-associated Disease Manmentioning
confidence: 99%